Effects of Spectral Shaping on Speech Auditory Brainstem Responses to Stop Consonant-Vowel Syllables - Rishiq, Dania; Harkrider, Ashley; Springer, Cary; Hedrick, Mark (Journal of the American Academy of Audiology, 2022)
Background Spectral shaping is employed by hearing aids to make consonantal information, such as formant transitions, audible for listeners with hearing loss. How manipulations of the stimuli, such as spectral shaping, may alter encoding in the auditory brainstem has not been thoroughly studied.Purpose The aim of this study was to determine how spectral shaping of synthetic consonant-vowel (CV) syllables, varying in their second formant (F2) onset frequency, may affect encoding of the syllables in the auditory brainstem.Research Design We employed a repeated measure design.Study Sample Sixteen young adults (mean = 20.94 years, 6 males) and 11 older adults (mean = 58.60 years, 4 males) participated in this study.Data Collection and Analysis Speech-evoked auditory brainstem responses (speech-ABRs) were obtained from each participant using three CV exemplars selected from synthetic stimuli generated for a /ba-da-ga/ continuum. Brainstem responses were also recorded to corresponding three CV exemplars that were spectrally shaped to decrease low-frequency information and provide gain for middle and high frequencies according to a Desired Sensation Level function. In total, six grand average waveforms (3 phonemes [/ba/, /da/, /ga/] X 2 shaping conditions [unshaped, shaped]) were produced for each participant. Peak latencies and amplitudes, referenced to prestimulus baseline, were identified for 15 speech-ABR peaks. Peaks were marked manually using the program cursor on each individual waveform. Repeated-measures analysis of variances were used to determine the effects of shaping on the latencies and amplitudes of the speech-ABR peaks.Results Shaping effects produced changes within participants in ABR latencies and amplitudes involving onset and major peaks of the speech-ABR waveform for certain phonemes. Specifically, data from onset peaks showed that shaping decreased latency for /ga/ in older listeners, and decreased amplitude onset for /ba/ in younger listeners. Shaping also increased the amplitudes of major peaks for /ga/ stimuli in both groups.Conclusions Encoding of speech in the ABR waveform may be more complex and multidimensional than a simple demarcation of source and filter information, and may also be influenced by cue intensity and age. These results suggest a more complex subcortical encoding of vocal tract filter information in the ABR waveform, which may also be influenced by cue intensity and age.
Keywords: speech-evoked auditory brainstem response; subcortical encoding; consonants; spectral shaping; amplification; hearing aids